A novel laser‐cut fully covered metal stent with anti‐reflux valve in patients with malignant distal biliary obstruction refractory to conventional covered metal stent. (26th April 2021) - Yamada, Yuto; Sasaki, Takashi; Takeda, Tsuyoshi; Mie, Takafumi; Furukawa, Takaaki; Kasuga, Akiyoshi; Matsuyama, Masato; Ozaka, Masato; Igarashi, Yoshinori; Sasahira, Naoki
Abstract: Background: Stenting against recurrent biliary obstruction (RBO) after placement of covered metal stent (CMS) for distal malignant biliary obstruction (MBO) is still challenging. This study investigated the feasibility of a novel laser‐cut fully CMS with anti‐reflux valve in patients with distal MBO refractory to conventional CMS. Methods: Patients who underwent Duckbill‐type metal stent (DMS) placement between June 2019 and May 2020 were included. Early complications, causes of RBO including non‐occlusion cholangitis, and time to RBO (TRBO) were evaluated. TRBO of DMS was also compared with that of previous CMS. Results: Thirty patients were included: pancreatic cancer/metastatic lymph nodes in 29 patients/one patient; duodenal stenosis in 13 patients. Technical and functional success were achieved in all patients. Mild cholangitis and mild pancreatitis developed in each one. Median follow‐up period was 167 days (range, 23‐527 days). RBO occurred in nine patients (30%): sludge formation in four patients, hemobilia in one patient, symptomatic distal stent migration in three patients, and non‐occlusion cholangitis in one patient. TRBO of DMS was significantly longer than that of previous CMS (median 224 days vs median 120 days, P  = .0025). DMS was successfully removed in all of six patients when re‐intervention was needed. Conclusions: Duckbill‐type metal stent might be safe and effective in patients with distal MBO refractory to conventional CMS. Abstract : Highlight Yamada and colleagues investigated the feasibility of a novel laser‐cut stent with anti‐reflux valve in 30 patients with distal malignant biliary obstruction refractory to conventional covered metal stents. The novel stent was safe and effective, with a significantly longer time to recurrent biliary obstruction than with other covered metal stents.